Construction of single-cell arrays and assay of cell drug resistance in an integrated microfluidic platform. Issue 23 (27th October 2016) - Pang, Long; Liu, Wenming; Tian, Chang; Xu, Juan; Li, Tianbao; Chen, Shu-Wei; Wang, Jinyi
Abstract : We describe an integrated microfluidic platform for the construction of single-cell arrays and analysis of drug resistance. Abstract : The cellular heterogeneity of tumors has played important roles in various tumor-related research areas and applications such as the cellular biology, metastasis and clinical diagnosis of tumors. Although several microfluidics-based single-cell separation and analysis techniques have been used in research into the cellular heterogeneity of tumors, further investigation is still required for studying the effect of the biomechanical ( e.g., size and deformability) heterogeneity of cells on their biological characteristics ( e.g., drug resistance and tumor-initiating features). Here, we established an integrated microfluidic platform for the construction of single-cell arrays and analysis of drug resistance. Using this device, high-throughput single-cell arrays could be easily obtained according to the biomechanical (size and deformability) heterogeneity of cells. To demonstrate the capability of the microfluidic platform, a proof-of-concept experiment was implemented by determining the vincristine resistance of single glioblastoma cells with different biomechanical properties. The results indicated that the biomechanics of tumor cells had significant implications for cell drug resistance; that is, small and/or more deformable tumor cells had higher drug resistance than large and/or less deformable tumor cells. This device provides a new approach for the isolation of single cells according to the different biomechanical properties of cells. Also, it possesses practical potential for studies of tumors on a single-cell level.